Kidney Replacement Therapy in COVID-19 Induced Kidney Failure and Septic Shock: A Pediatric Continuous Renal Replacement Therapy [PCRRT] Position on Emergency Preparedness With Resource Allocation - Raina, Rupesh; Chakraborty, Ronith; Sethi, Sidharth Kumar; Bunchman, Timothy (Frontiers in Pediatrics, 2020)
The recent worldwide pandemic of COVID-19 has had a detrimental worldwide impact on people of all ages. Although data from China and the United States indicate that pediatric cases often have a mild course and are less severe in comparison adults, there have been several cases of kidney failure and multisystem inflammatory syndrome reported. As such, we believe that the world should be prepared if the severity of cases begins to further increase within the pediatric population. Therefore, we provide here a position paper centered on emergency preparation with resource allocation for critical COVID-19 cases within the pediatric population, specifically where renal conditions worsen due to the onset of AKI.